Prior Interpersonal Violence Exposure and Experiences During and After a Disaster as Predictors of Posttraumatic Stress Disorder and Depression Among Adolescent Victims of the Spring 2011 Tornadoes. Issue 23 (November 2020) - Resnick, Heidi; Zuromski, Kelly L.; Galea, Sandro; Price, Matthew; Gilmore, Amanda K.; Kilpatrick, Dean G.; Ruggiero, Kenneth
The purpose of the current report was to examine prior history of exposure to interpersonal violence (IPV), as compared with prior accident or prior disaster exposure, experiences during and after a disaster, and demographic variables as predictors of past month posttraumatic stress disorder (PTSD) and depression severity among adolescents exposed to the tornadoes in Alabama and Missouri. IPV exposure has been consistently identified as a unique category of potentially traumatic events (PTE) that significantly increases risk for development of PTSD and other difficulties relative to other event types among adolescents. A population-based sample of adolescents and caregivers ( N = 2, 000) were recruited randomly from tornado-affected communities in Alabama and Joplin, Missouri. Participants completed structured telephone interviews on an average of 8.8 months posttornado. Prior history of IPV was prevalent (36.5%), as was reported history of accidents (25.9%) and prior disaster exposure (26.9%). Negative binomial regression analyses with PTSD and depression symptom counts for past month as outcome variables indicated that history of predisaster IPV was most robustly related to PTSD and depression symptoms, such that those with a history of IPV endorsed over 3 times the number of symptoms than those without IPV history. Final model statistics indicated that female gender, physical injury to caregiver, concern about others' safety, prior disaster, prior accident, and prior IPV exposure were also related to PTSD. Predictors of depression symptoms were similar with the exception that concern about others' safety was not a predictor and age was a predictor in the final model. It is important to evaluate potential additive effects of IPV history in addition to recent disaster exposure variables and to consider such history when developing interventions aimed to reduce or prevent symptoms of PTSD and depression among adolescents recently exposed to disaster.